DAMPAK PENERAPAN H.R.4380, DALAM THE U.S. MANUFACTURING ENHANCEMENT ACT OF 2010 BAGI INDONESIA - Aziza Rahmaniar Salam (Buletin Ilmiah Litbang Perdagangan, 2011)
This study aims at reviewing the Indonesia trade performance on several products included in the list of the new Act, the u.s manufacturing enhancement Act of 2010. Using secondary data collected from The Central Board of Statistics and the World bank, it was found that Indonesia has benefits from the tariff reduction facility under the US Manufacturing Enhancement Act of 2011. The benefit is in increasing non-oil product exports to US. Also,it is shown that there is an increasing Indonesia’s shares in US market especially for products with tariff heading 2934.99, 3808.93, 3907.99, 3917.40, 4016,99 and 4202.92